Decoding the WHO Global Tuberculosis Report 2024: A Critical Analysis of Global and Chinese Key Data - Zhi Chen; Tao Wang; Jingli Du; Lin Sun; Guirong Wang; Ruizi Ni; Yajing An; Xueting Fan; Yufeng Li; Rui Guo; Lirong Mao; Wei Jing; et al. (Zoonoses, 2025)
The World Health Organization (WHO) “Global Tuberculosis Report 2024” underscores the ongoing challenges and progress in the global fight against tuberculosis (TB). Despite a slowdown in the annual increase in TB cases and a decline in TB-related deaths, the disease remains a significant public health threat with 10.8 million new cases reported in 2023. The report reveals a persistently high burden of TB, especially in low- and middle-income countries, and highlights the escalating issue of drug-resistant TB. The report also emphasizes the critical need for increased funding, improved diagnostics, and more effective TB treatment regimens. The impact of the COVID-19 pandemic on TB control has been substantial, disrupting healthcare services and exacerbating existing challenges. This paper provides an in-depth interpretation of the report, analyzes global TB trends, updates the status of drug-resistant TB, discusses the intersection between TB and HIV, and summarizes the implications of the pandemic on TB control efforts. The report concludes with a call for intensified global action, including increased investment in research and innovation, to achieve the United Nations’ Sustainable Development Goals related to TB control. The stakes are high, but with concerted efforts, the goal of ending the TB epidemic is within reach.